Implementation Of The 2013 Curriculum In Al-Mustaqim Lawang Malang - Safitri Mujanah; Maskuri Bakri; Dwi Fitri Wiyono; Ali Ashar (Institut Agama Islam An-Nawawi Purworejo, 2022)
The ability to read the Qur'an of students is a realization of faith in the Book of Allah (Al-Qur'an). The command to read the Qur'an has been ordered since the revelation of the first time QS. Surah Al-Alaq verses 1-5 which has a message for Muslims to read. To equip students' ability to read the Qur'an, the 2013 curriculum was implemented in the lessons of Al-Qur'an Hadith, legal material for reading gharib towards BTQ co-curricular activities through planning, implementation process and evaluation system. Through this gharib knowledge, students gain knowledge in reading the Qur'an. So that the quality of reading the Qur'an of students increases. The purpose of this study was to discuss, analyze and provide interpretations of the planning, implementation process and evaluation system of the 2013 curriculum in Al-Qur'an Hadith lessons at Madrasah Tsanawiyah One Roof Al-Mustaqim Lawang Malang. The research method uses a qualitative approach to the type of observational case study research. The data collection method used is using observation, interviews, field notes and documentation. Based on the data obtained, it was analyzed by collecting, condensing, presenting data and drawing conclusions. The results showed that: 1) Planning the implementation of the 2013 curriculum in Al-Qur'an Hadith lessons at MTs Satu Atap Al-Mustaqim Lawang Malang was carried out through the formulation of objectives, cognitive analysis and mapping processes, targets, syllabus, material development, learning strategies and lesson plans. 2) The process of implementing the 2013 curriculum in Al-Qur'an Hadith lessons at MTs Satu Atap Al-Mustaqim Lawang Malang through the introduction stage, the core stage and the closing stage. 3) Evaluation system for 2013 curriculum implementation in Al-Qur'an Hadith lessons at MTs Satu Atap Al-Mustaqim Lawang Malang using authentic assessment which includes knowledge competency assessment, attitude competency assessment and skills competency assessment.